Key questions about aortic insufficiency in patients with durable left ventricular assist devices - Calin, Eliza; Ducharme, Anique; Carrier, Michel; Lamarche, Yoan; Ben Ali, Walid; Noly, Pierre-Emmanuel (Frontiers in Cardiovascular Medicine, 2022)
The development of the latest generation of durable left ventricular assist devices (LVAD) drastically decreased adverse events such as pump thrombosis or disabling strokes. However, time-related complications such as aortic insufficiency (AI) continue to impair outcomes following durable LVAD implantation, especially in the context of long-term therapy. Up to one-quarter of patients with durable LVAD develop moderate or severe AI at 1 year and its incidence increases with the duration of support. The continuous regurgitant flow within the left ventricle can compromise left ventricular unloading, increase filling pressures, decrease forward flow and can thus lead to organ hypoperfusion and heart failure. This review aims to give an overview of the epidemiology, pathophysiology, and clinical consequences of AI in patients with durable LVAD.